Heparin Elimination in Patients with Liver Cirrhosis - Teien, Arne N. (Thrombosis and Haemostasis, 1977)
Heparin (100 U/kg body-weight) was injected intravenously, and heparin concentration in plasma determined by polybrene titration. Mean heparin half-life was 117.8 min in a group of patients with liver cirrhosis and normal renal function (n = 6) as compared to 74.0 min in the normal group (n = 6). The difference between the two groups is statistically significant (p ≈ 0. 02). Heparin half-life was correlated to galactose half-life in the patients (r = 0.83, p = 0. 05). The findings suggest that heparin is metabolized in the liver. There was a significant fall in antithrombin III activities in the normals, but not in the patients. A possible explanation may be that the normal liver removes heparin bound to antithrombin III, and that this function is impaired in liver cirrhosis.